2020
DOI: 10.1016/j.physbeh.2019.112744
|View full text |Cite
|
Sign up to set email alerts
|

Introducing eccentric cycling during a multidisciplinary weight loss intervention might prevent adolescents with obesity from increasing their food intake: The TEXTOO study

Abstract: This is a repository copy of Introducing eccentric cycling during a multidisciplinary weight loss intervention might prevent adolescents with obesity from increasing their food intake: The TEXTOO study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 41 publications
(70 reference statements)
1
20
0
Order By: Relevance
“…First, in line with previous studies conducted in similar populations [8][9][10], our results confirm a significant increase of the adolescents' food intake in response to the weight loss intervention (ad libitum lunch intake as well as a tendency for total ad libitum energy intake), mainly due to an increased fat and protein intake. Interestingly, this higher energy consumption is accompanied by higher fasting sensations of hunger, prospective food consumption, and a craving to eat, as well as a reduced feeling of fullness.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…First, in line with previous studies conducted in similar populations [8][9][10], our results confirm a significant increase of the adolescents' food intake in response to the weight loss intervention (ad libitum lunch intake as well as a tendency for total ad libitum energy intake), mainly due to an increased fat and protein intake. Interestingly, this higher energy consumption is accompanied by higher fasting sensations of hunger, prospective food consumption, and a craving to eat, as well as a reduced feeling of fullness.…”
Section: Discussionsupporting
confidence: 91%
“…Multidisciplinary interventions combining physical activity, nutritional guidelines, and psychological support are actually recommended [4] and have been shown to be effective (at least in the short term) in inducing significant body weight and body composition [5], physical fitness [5], cardio-metabolic profile [6], and health-related quality of life [7] improvements, among others. Some recent results have indicated, however, that adolescents with obesity increase their daily energy intake in response to such interventions [8][9][10], which might contribute to the usually-observed post-treatment weight regain. While the role played by adolescents' cognitive profiles has been established to partly account for these appetitive responses to weight loss, the potential implications of their cardio-metabolic profiles remain beyond any doubt.…”
Section: Introductionmentioning
confidence: 99%
“…In adolescents with obesity, eccentric cycling exercise as part of a 12-week inpatient multidisciplinary weight loss intervention increased the relative preference for high-fat food and increased both the relative preference and implicit wanting for savory food, whereas no changes were observed in response to concentric exercise training [63]. Another study in adolescents with obesity showed that during a 10-month inpatient multidisciplinary weight loss intervention including physical activity, liking for food in the hungry state increased from baseline to 5 months, then returned to baseline values at 10 months, whereas liking for food in the fed state decreased (Miguet et al, under review).…”
Section: Chronic Exercise Training Studiesmentioning
confidence: 94%
“…More recent studies in the adult population have shown that increases in dietary intake accompanied by exercise initiation is a mechanism often observed that contributes to compensation [ 129 , 130 ]. In adolescents with obesity, energy intake ad libitum was greater at the end of long-term exercise programs (≥12 weeks) compared to baseline, with compensation being a characteristic of restrained eaters [ 131 , 132 ]. Additionally, the timing of exercise in relation to meal also appears to influence prospective food consumption in adolescents with obesity; although no significant differences were found in ad libitum total energy intake after 60 or 180 min from an exercise session (30 min), exercising closer to lunch time (60 min) led to a reduction of 170 kcal in energy intake [ 133 ].…”
Section: Adipose Tissue Developmentmentioning
confidence: 99%